Assessing Presentation Skills in STEAM Project-Based Learning: A Longitudinal Analysis Using Rasch Modeling - Hidayat, Panji; Oktova, Raden; Sukarelawan, Moh. Irma; Rohman, Fatkhur (Jurnal Pendidikan Progresif, 2025)
Assessing Presentation Skills in STEAM Project-Based Learning: A Longitudinal Analysis Using Rasch Modeling. Project presentation is a crucial element in PjBL learning, as it allows students to demonstrate their understanding of the material studied and the ability to convey project ideas and results effectively. Objectives: This study aims to analyse students' presentation performance in teaching using the Project-based Learning approach. Methods: The type of research used is a quasi-experimental design with a time series approach. Respondents involved in this study were 22 prospective elementary school teacher students. The groups assessed were randomly selected using a lottery system. The instrument used to assess group presentation skills consists of 11 items, and each item uses a 5-point Likert rating scale. Presentation performance data was analysed using the Logit Value of Item (LVI) technique combined with the Wright map. Findings: Group presentation performance experienced variations in improvement over time, with some skills showing an increasing trend and others showing a decreasing trend. Conclusion: The implication of this study, in terms of presentation performance, is that although there is variation in the improvement of student presentation skills over time, analysis using Rasch modelling can provide greater insight into the factors that influence presentation quality and help identify areas that require improvement in Project-based Learning teaching. Keywords: logit value of item, presentation skills, rasch model, STEAM, wright map.